2000
DOI: 10.1007/s11746-000-0134-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nonvolatile lipid oxidation products in vegetable oils by normal‐phase high‐performance liquid chromatography with mass spectrometric detection

Abstract: Nonvolatile triacylglyceride (TAG) oxidation products play an important role in the oxidative degradation of lipids. They serve as a reservoir of oxygen-containing species and hence can act as off-flavor precursors or as initiators for further oxidation reactions. Possible nonvolatile lipid oxidation products are TAG with a hydroperoxy, hydroxy, epoxy, or oxo (ketone or aldehyde) group or combination of these groups. The breakdown of TAG hydroperoxides yields nonvolatile glyceride species with two intact fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 10 publications
0
47
0
Order By: Relevance
“…On the basis of previous work with standard oxotriacylglycerols (22,42), the earlier eluted peak was attributed to an aldehyde in the secondary position and the later eluted peak to an aldehyde in the primary position of the oxidized triacylglycerol molecule. A functional group in the sn-2 position is known to exert higher polarity than a similar group in the sn-1 or sn-3 position of the triacylglycerol molecule (22,43,44).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…On the basis of previous work with standard oxotriacylglycerols (22,42), the earlier eluted peak was attributed to an aldehyde in the secondary position and the later eluted peak to an aldehyde in the primary position of the oxidized triacylglycerol molecule. A functional group in the sn-2 position is known to exert higher polarity than a similar group in the sn-1 or sn-3 position of the triacylglycerol molecule (22,43,44).…”
Section: Discussionmentioning
confidence: 85%
“…These compounds could have been formed in a termination reaction between a tert-butylhydroperoxy radical and an alkenyl radical or between a lipid hydroperoxy radical and the tert-butyl radical. The formation of the tert-butyl derivatives of the lipid hydroperoxides has a precedent in the existence of di-tert-butyl peroxide (40), as well as in the formation of cyclic peroxides during decomposition of linoleate hydroperoxides (31,48) and tocopherol adducts (42). Furthermore, Miyashita et al (31) have demonstrated that oxygenation of methyl linoleate hydroperoxides yields dimers composed of octadecadienoate and octadecenoate moieties crosslinked through either ether or peroxy linkages across the 9-or 13-positions.…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62][63][64][65] In our study, NaI appeared to be ideal for the detection of these neutral lipids in the mixture of chloroform and methanol. NaI has been used as the additive by two groups for enhanced ESI-MS detection of polar plasmenyl phosphati- 66 and phosphatidylethanolamine 67 and one group for nonpolar triacylglycerols 68 ; however, no rationale for choosing NaI over other sodium salts as the additive was offered by these groups. We attribute such enhancement primarily to two reasons.…”
Section: Nai Additive For Highly Sensitive Esi-ms Detection Of Intactmentioning
confidence: 99%
“…The putative assignment of non-identified peaks (NIP) to core aldehydes and other non-volatile oxidation products was excluded by comparing to the NP-HPLC data made available by SteenhorstSlikkerveer et al [49]. Table 3.…”
Section: (Esi-ms-msmentioning
confidence: 99%